Insulin resistance-associated decreases in left ventricular diastolic function are strongly modified by the extent of concentric remodeling in a community sample. (1st October 2016) - Peterson, Vernice; Norton, Gavin R.; Raymond, Andrew; Libhaber, Carlos D.; Millen, Aletta M.E.; Majane, Olebogeng H.I.; Maseko, Muzi J.; Woodiwiss, Angela J.
Abstract: Background: Whether excess adiposity, associated metabolic abnormalities or alternative risk factors for left ventricular (LV) diastolic function are modified rather than mediated by geometric LV remodeling, is uncertain. Methods: Echocardiographic LV mass index (LVMI), relative wall thickness (RWT) and diastolic function (lateral and septal wall myocardial tissue lengthening at the level of the mitral annulus [e′] [n = 430], ratio of early-to-late transmitral blood flow velocity (E/A), and E/e′ [n = 430]) were determined in 737 randomly recruited participants of a community-based study (43% obese). Results: Independent of LVMI and confounders, indexes of adiposity and the homeostasis model of insulin resistance (HOMA-IR) were independently associated with LV diastolic function (p < 0.05). In addition, RWT was independently associated with LV diastolic function (p < 0.002). Importantly, an independent interaction between HOMA-IR and RWT, but not between blood pressure or age and RWT, was related to LV diastolic function (p < 0.05). This translated into an independent relationship between HOMA-IR and lateral e′ (partial r = − 0.17, p < 0.02), septal e′ (partial r = − 0.14, p = 0.05), E/A (partial r = − 0.17, p < 0.005) and E/e′ (partial r = 0.19, p < 0.01) in those with RWT above, but a lack of relationship between HOMA-IR and LV diastolic function (p > 0.59) in those with RWT below the median for the sample. Similarly, HOMA-IR was independently associated with LV diastolic dysfunction in those with RWT above (p < 0.05) but not below (p > 0.19) the median for the sample. Conclusions: The relationship between insulin resistance, but not alternative risk factors and LV diastolic function is markedly modified by the presence of a more concentrically remodeled LV.